Experimental study on flow heterogeneity of shale bedding fractures based on full-diameter cores - Juhui ZHU; Jing ZENG; Zhoumei GENG; Yongming LI; Tengfei WANG; Deqi LI; Yong PAN; Juan WANG (Petroleum Exploration and Development, 2023)
A self-designed full-diameter core experimental facility was used to evaluate the flow heterogeneity of bedding fractures at four radial directions under different closure pressures and injection rates, using full-diameter cores retaining original natural bedding fractures. The distribution morphology of bedding surface affects the conductivity of bedding fractures, and the flow capacity of bedding fractures in four radial directions varies greatly with the closure pressure and injection rate. The rougher the fracture surface, the greater the flow capacity varies with the closure pressure. For unsupported bedding fractures, the mean percentage error (MPE) of the conductivity in four radial directions increase gradually with the increase of the closure pressure. This phenomenon is especially prominent in deep rock samples. It is indicated that the flow heterogeneity of bedding fractures tends to increase with the closure pressure. When proppant is placed in the fracture, at a low closure pressure, due to the combined effects of self-support of rough fracture surface, proppant instability and uneven proppant placement, the flow heterogeneity is greater than that when proppant is not placed at the same closure pressure; however, with the increase of the closure pressure, the proppant becomes compact and stable, and the flow heterogeneity is mitigated gradually.